Hybrid Best-Fit Heuristic for Energy Efficient Virtual Machine Placement in Cloud Data Centers - Jangiti, Saikishor; V, Vijayakumar; V, Subramaniyaswamy (EAI Endorsed Transactions on Energy Web, 2020)
Cloud Service Providers (CSPs) offers Information Technology services like infrastructure and software to users on a pay as you go basis. Energy consumption is one of the significant challenges faced by Cloud Service Providers (CSP). Virtual Machine (VM) placement is an energy-efficient practice performed in the cloud datacenters. Best-Fit Decreasing (BFD) is a VM placement and is known to give a near-optimal solution in a reasonable time by sorting the VMs in decreasing order. We propose a Hybrid Best-Fit (HBF) Heuristic for VM placements. Experimental results show that HBF is consuming 2.516% and 3.392% less energy compared to Best-Fit and BFD heuristics.
Keywords: VM Placement; Best Fit Decreasing; Hybrid Heuristics